Milk production in commercial cattle dairy farms in Kosova - Bytyqi, Hysen; Rrustemi, M.; Mehmeti, Hajrip; Kryeziu, A.; Gjinovci, V.; Gjonbalaj, Muje (2009)
A study research was carried out in comercial dairy farms in Kosovo with the aim to contribute to the understanding of the situation of milk production and factors affecting milk productivity. Seventeen dairy cattle farms were selected for the study. The fresh milk samples were collected and record analyses were done according to the International Committee for Animal Recording using the A4 standard method, and were carried out from August 2007 till September 2008. Meanwhile, 4694 milk samples from 461 individual cows were collected. Depending on the cow breed, daily milk yield was very different (P < 0.0001) ranging from 18.92 0.22 to 12.34 0.53. Effect of the farm and lactation number was also very significant (P < 0.0001), showing that there are huge managment variation from farm to farm (for about 14.87 kg/day) and during different lactations (16.91 0.26 to 18.43 0.24 kg/day). According to this study, although in generaly milk yield was very much constant, in some months of year cows in Kosovo tend to produce more milk. Huge differences (about 29.06%) were noticed also within the same breed comparing the current production in Kosovo and from cow breed origine in Austria. It was concluded that low milk yield was achieved for all breeds compared to their genetic potential. Furthermore, according to current dairy farm management condition in Kosovo, more favorable breeds tend to be dual purpose breeds compare to more milk specialized ones
Bibliografija: 14 jed
Keywords: Proizvodnja mlijeka -- Mljekarska farma -- Laktacija -- Prinos mlijeka; Kosovo